equity capital should be improved by raising more share capital, retaining more profits and deriving share premium by selling additional equity shares to the general public at price greater than the nominal value. - Douglas Ogechukwu, Ibeh (Journal of Accounting and Financial Management, 2026)
This study examines the effect of firm attributes and ownership structure on stock returns of listed consumer goods companies in Nigeria. Adopting an ex-post facto research design, the study analyzed data from 14 listed consumer goods companies on the Nigerian Exchange Group from 2013 to 2024. Using panel regression analysis, the study found that firm attributes collectively have a positive relationship with share returns, though only firm size shows a statistically significant effect. Regarding ownership structure, the evidence is mixed: managerial ownership reveals a negative insignificant relationship with share returns, institutional ownership shows a positive but insignificant relationship, and concentrated ownership exhibits an insignificant negative relationship. The findings suggest that investors and managers should focus on strategic non-current assets to enhance firm size effectiveness, while maintaining balanced ownership structures that promote long-term investment culture. The study contributes to understanding the unique dynamics of the Nigerian consumer goods sector and provides insights for investment decision-making in emerging markets.